A case of moderate depression with somatic symptoms and incidental finding of retrocerebellar arachnoid cyst - Mukherjee, Sumit; Bhattacharya, Aparupa (Asian Journal of Medical Sciences, 2021)
Arachnoid cysts are benign space-occupying brain lesions that contain cerebrospinal fluid which is mostly congenital in origin. Cases are mostly detected incidentally on neuro-imaging and neuropsychiatric manifestations are less common and under-recognized. Arachnoid cyst sometimes may be associated with seizure, headache, cranial nerve deficits, hydrocephalus, etc. A 23-year-old married female from rural India presented with headache, insomnia, low mood, lethargy, persisting for the past 6 months without any obvious stress factors. She also informed that she had few episodes of unresponsiveness without any features such as tongue biting, confusion, injury, or involuntary micturition and defecation. Her EEG report was within normal limit and MRI report confirmed the presence of Retro-cerebellar Arachnoid cyst in and around midline. Detail neurological and ophthalmological examination was done and findings were within normal limits. She was treated with Amitriptyline, Pregabalin, and Paracetamol. Psychotherapy was initiated for adequate management of her depressive symptoms and responded well. It can be emphasized that patients who are reporting with symptoms such as headache a detail evaluation should be done to find out organic etiology. Depressive and cognitive symptoms and its association with arachnoid cyst may depend upon the location of the lesion and further research is required to establish its causal relationship.